Improving business objectives by reducing testing in the transition from development to production. (18th June 2020) - Dror, Shuki
Abstract: This work focuses on finding a balance between the requirements to maintain product initial failure rate and the need to improve business objectives. We build on quality function deployment (QFD) by developing an innovative methodology for reducing testing in the transition from development to production. The methodology allows the number of tests to be reduced, without increasing the risk of lowering product quality. Our methodology assumes that testing affects product initial failure rate and business objectives simultaneously. Hence, a QFD‐based methodology comprising two matrices is developed. Matrix 1 translates the desired improvement in the business objectives into the relative importance of the various test types. Matrix 2 translates the product failure improvement needs into the relative importance of the various test types. We implement the methodology in a company developing and manufacturing medical devices. We find that the events "vital tests concerning the business objectives" and "vital tests concerning the failures in products" are mutually exclusive. Hence, we can conclude that it is possible to achieve a significant reduction in the number of tests conducted on the medical devices. The results show that the tests that can be reduced are those that will not affect product initial failure rate but that do have a significant impact on business objectives.